PENGARUH STORY TELLING TERHADAP PERILAKU KESULITAN MAKAN PADA ANAK USIA PRASEKOLAH - Lismaysarah " Pasaribu; Ganis " Indriati; Safri " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Research about story telling influence difficulty eating behavior in preschool-aged children conducted in TK Negeri Pembina I Pekanbaru. Design of research is experimental with pretest approach quasy-posttest with control group. The sample of this research totalled 30 respondents taken by a purposive sampling technique. Measuring instrument used is the observation sheets to gauge the behavioural difficulties eating children. Analysis of test data using independent sample t test and the dependent sample t test. The results showed that the average value of behavioral difficulty eating before the given story telling on the experimental group was 4.40 while in the control group is 3.47. The average value of behavioral difficulty eating after the given story telling on the experimental group was 4.40 while in control group was 3.47. The test results of the study dependent sample t test obtained p value (0.000) < alpha (0.05) then H0 is rejected so there are incentives that influence before and after the given story telling against the difficulty of eating behavior in preschool-aged children in TK Negeri Pembina I Pekanbaru. Keywords: Difficulty of eating behavior, story telling, preschool-aged children